Design and characterization of a long period fiber grating based sensor for mercury (ii) ions detection - Tan, Shin Yinn (2018)
Water is known as a very essential substance that all living beings cannot survive without, hence the purity of water has become a crucial issue. Recently, there have been enough cases reported in which the pollution of water bodies has become an appalling issue, especially those caused by heavy metals. Water pollution not only affects the nature ecosystems, but also causes harmful effects to human health. One of the heavy metals that requires attention is mercury. Many fresh and sea water areas have been reported to be contaminated by mercury, which is then ingested by aquatic life and pass through the food chain, ultimately reaching to humans. The exposure to mercury, even in small amounts, can lead to serious health problems. For example, the neurological development, renal organ systems and gastrointestinal functions of human bodies can be destroyed if overly exposed to mercury. Due to this, the monitoring of mercury content in water is important and a variety of measurements have been proposed and demonstrated over the years. One of the commonly used sensors in monitoring mercury is opticalbased sensors as it offers a variety of advantages, including its small size, light weight, immunity to electromagnetic interference and its ease of signal transmission. However, most optical-based sensors required the measurands to be collected from the site before they can be tested in the laboratory. Due to this, the proposed sensors were only limited to a short and quick laboratory detection. This project explores the possibility of extending the detection outside the laboratory. The project proposed the use of an electric arc-induced Long Period Fiber Grating (LPFG) as the optical-based sensor for mercury detection because past research have proven that LPFG can be deployed kilometers away where an electric source is not needed at the sensing point. In other words, the application of LPFG can be extended to the real environment. This particular property of LPFG will help overcome the limitation of previously proposed sensors, where they were only limited to laboratory testing. Also, the unique property of LPFG, i.e. its sensitivity to external index, is another reason why LPFG is proposed as the optical-based sensor for monitoring mercury content in this project, as a slight change in the surrounding refractive index caused by mercury content can be investigated through its response. Throughout the years, not much research has been done on using LPFG as a mercury sensor. Hence, the techniques to enhance its sensitivity and the sensing agent that can tailor the surface of LPFG are explored in this research so that the LPFG will respond to the presence of mercury in water. Another important aspect that should be considered in environmental studies such as water monitoring is long-term detection because it allows the collection of background data over a longer period of time. Also, it helps to reveal important trends which can provide researchers with more solid proof in understanding environmental parameters. However, most of the proposed fiber sensors including LPFG were limited to short-term detection. When it comes to long-term monitoring, LPFG without protection may not be suitable to be used due to its brittle silica-based structure. Hence, another limitation is found in this aspect. In this project, a structure that can be used to protect the modified LPFG and prevent it from being broken by the harsh environment was constructed as well. The structure constructed in this project was similar to the structure of (Diffusive Gradient in Thin Films) DGT, which was proposed in 1994 for long-term detection purposes. With the protection offered by this structure, the LPFG can be used to monitor mercury (II) ions over a longer duration as the structure helps to overcome the weakness of LPFG, i.e. limited lifespan. In conclusion, the purpose of this project is to solve both the limitations discussed earlier, i.e. to extend the sensing application of LPFG to outside of laboratory and to prolong the lifespan of LPFG for long term monitoring. A hybrid sensor which combined the features of both LPFG and DGT was proposed and demonstrated in this research to allow the application of real-time and long-term monitoring of mercury (II) ions in water. In the beginning stage of the research, the sensitivity of LPFG towards refractive index was enhanced. The shifting of the resonant wavelength of the LPFG in response to external refractive index was increased by applying thin film coating method. Also, the transmission loss of the LPFG was enhanced by introducing double-pass configuration into the experiment setup. The improved LPFGs were then coated with gold nanoparticles and tested with different concentrations of mercury (II) ions solution. From the study, the resonant wavelengths of the coated LPFGs shifted to longer wavelength and its transmission power increased when it was exposed to mercury (II) ions. This proves that the LPFGs were able to detect the presence of mercury (II) ions with the coating agent. In the final stage of the research, a hybrid LPFGDGT monitoring sensor system was constructed and demonstrated. The sensor was again experimented with different concentrations of mercury (II) solutions. Similarly, the resonant wavelength of the sensor shifted to longer wavelength and the transmission power increased. This result proves that the designed LPFG-DGT hybrid sensor was capable of performing real-time and long-term monitoring of mercury (II) ions in water bodies.